2021
DOI: 10.1111/ajt.16174
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 trial of human islet-after-kidney transplantation in type 1 diabetes

Abstract: Allogeneic islet transplant offers a minimally invasive option for β cell replacement in the treatment of type 1 diabetes (T1D). The CIT consortium trial of purified human pancreatic islets (PHPI) in patients with T1D after kidney transplant (CIT06), a National Institutes of Health–sponsored phase 3, prospective, open‐label, single‐arm pivotal trial of PHPI, was conducted in 24 patients with impaired awareness of hypoglycemia while receiving intensive insulin therapy. PHPI were manufactured using standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 35 publications
5
68
0
Order By: Relevance
“…In this trial, similar outcomes (e.g. HbA1c < 6.5% + absence of SHEs) were achieved in 62.5%, 58.3%, and 45.8% of patients at 1‐, 2‐, and 3‐years post‐IT 17 . Notably, awareness of hypoglycemia was almost completely restored at 1‐year post‐IT 17 .…”
Section: The Path To Clinical Successsupporting
confidence: 60%
See 1 more Smart Citation
“…In this trial, similar outcomes (e.g. HbA1c < 6.5% + absence of SHEs) were achieved in 62.5%, 58.3%, and 45.8% of patients at 1‐, 2‐, and 3‐years post‐IT 17 . Notably, awareness of hypoglycemia was almost completely restored at 1‐year post‐IT 17 .…”
Section: The Path To Clinical Successsupporting
confidence: 60%
“…HbA1c < 6.5% + absence of SHEs) were achieved in 62.5%, 58.3%, and 45.8% of patients at 1‐, 2‐, and 3‐years post‐IT 17 . Notably, awareness of hypoglycemia was almost completely restored at 1‐year post‐IT 17 . Recent reports from the integrated UK programme, 18 San Raffaele Hospital in Milan 19 presented at the International Pancreas and Islet Transplant Association's congress in 2019, and from the Edmonton group presented at the 80th Scientific Session of the American Diabetes Association 20 consistently show substantial improvement in glycemic control, reductions in insulin doses and a nearly complete abrogation of SHEs.…”
Section: The Path To Clinical Successmentioning
confidence: 97%
“…According to the latest CITR annual report (10 th Annual Report, released in January 2017), the percentage of patients remaining insulin-independent after one year is approximately 50%, and a drop to 25% is observed after five years. A drop in insulin-independency was also reported by the more recent phase 3 CIT trial of human islet-after-kidney transplantation (4), where only 16.7% of the patients retained insulin independence three years after transplantation. These percentages are much lower than what was reported for patients undergoing total pancreas transplantation.…”
Section: Why the Need For Stem-cell Based Therapy In Diabetes?supporting
confidence: 59%
“…37 Similarly, a recent single-arm phase 3 study of IAK recipients found significantly reduced diabetes distress and fear of hypoglycaemia scores up to 3 years post-transplant compared with pre-transplant scores. 48 Improvement is particularly seen for diabetes specific QoL assessments and those relating to hypoglycaemia fears, anxiety scores and depression scores in islet transplant alone (ITA). While improvements in QoL scores were clear for those receiving ITA, there were no significant differences in QoL scores in SIK/IAK recipients.…”
Section: Graft Assessments and Outcomesmentioning
confidence: 99%